Fragilidade financeira externa no Brasil: evolução recente e impactos sobre a taxa de juros - Daniel Chiari Barros (2008)
The main objective of this work is to analyze the evolution of the external financial fragility of the Brazilian economy during the period 1990-2006. In order to achieve this goal, a review in the literature regarding external financial fragility is made, having Minskys financial instability hypothesis as a starting point. Afterwards, the index of external financial fragility (IFE) developed by Paula and Alves Jr. (1999) will be calculated, serving as a basis for the analysis. In order to verify the observations made by the IFE, the behavior of some of the periods main external solvency indicators will be presented. As a second objective, we investigate the impact of the financial fragility on the domestic interest rate and, consequently, on the Brazilian economic performance. For this, a VAR model will be estimated for the years of 1994 to 2006, in order to capture the impact of the external financial fragility on the domestic interest rate. The empirical result, although not very robust, suggests a positive correlation between these variables.